Influence of comercial on the vegetative propagation of Echeveria lilicina Kim. & Moran (Research, Society and Development, 2022)
As they present remarkable characteristics, easy to grow and resistant to water deficit, among the succulent family (Crassulaceae), we can mention the genus Echeveria, with a great interest in its commercialization. Its propagation method is via leaf cuttings, however, studies are needed to assist in faster rooting, through products, such as the use of different commercial rooters. Therefore, the objective of this work was to evaluate the response of different commercial rooters in the number of shoots, amounts of roots and length of the largest root in cuttings of leaves of Echeveria lilacina Kimn. & Moran. The experiment consisted of 7 treatments with 5 replications, as follows: (T1) Control (1 L of pure water); (T2) Sacrop® (1 mL of product to 1 L of water); (T3) Forth® (100 mL of product to 1 L of water); (T4) Vitaplan® (100 mL of product to 1 L of water); (T5) Seacrop® (1 mL of product to 1 L of water + applications every 10 days); (T6) Forth® (100 mL of the product for every 1 L of water + application every 10 days) and (T7) Vitaplan® (100 mL of the product for every 1 L of water + application every 10 days), being used the completely randomized design and the means submitted to the Tukey test at 5% probability. It was concluded that the use of inducing products did not provide a significant effect on the induction of sprouting or rooting of this species, and the control treatment (T1) presented the best result for the longest root length.